Preparation method of high-temperature-resistant and high-wear-resistant waterproof moisture-permeable film

A covalent bond interface is formed in the waterproof and breathable membrane through a gradient coagulation bath process, which solves the problem of insufficient high temperature resistance and wear resistance caused by weak interface bonding in the existing technology, and achieves improved structural stability and functionality of the material under high temperature and wear conditions.

CN120662154APending Publication Date: 2025-09-19ANTA (CHINA) CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510834748.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-20
Publication Date
2025-09-19

AI Technical Summary

Technical Problem

Existing waterproof and breathable membranes have insufficient performance under high temperature and wear conditions, mainly because the interface between the polymer matrix and the reinforced fiber skeleton relies on physical entanglement and lacks stable covalent bond bonding, resulting in interfacial stress concentration and rapid material wear.

Method used

A gradient coagulation bath process is used to form a covalent bond interface between the fiber skeleton and the polyurethane resin. The interfacial chemical reaction rate is controlled by using a weak non-solvent system of ethanol and ethyl acetate, and phase separation is driven in a strong non-solvent system of water and dimethylformamide to form a stable microporous structure.

Benefits of technology

It significantly improves the high temperature resistance and wear resistance of the waterproof and breathable membrane, effectively withstands thermal expansion stress and transfers stress through the covalent bond interface, avoids interface peeling and wear, and maintains the structural integrity and functionality of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120662154A_ABST
    Figure CN120662154A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-temperature-resistant and high-wear-resistant waterproof moisture-permeable membrane, which comprises the following steps: step 1, filling pores of a fiber skeleton with active groups on the surface with a membrane casting solution containing polyurethane resin and a solvent to form a complex; step 2, immersing the complex in a first liquid environment formed by mixing ethanol and ethyl acetate so as to form a covalent bond interface between the fiber skeleton and the polyurethane resin; and step 3, immersing the complex treated in the step 2 into a second liquid environment formed by mixing water and dimethylformamide so as to form a polyurethane matrix with a microporous structure in pores of the skeleton. The preparation method can improve the high temperature resistance and wear resistance of the waterproof moisture-permeable film prepared by a wet film forming process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of waterproof and breathable membranes, and in particular to a method for preparing a high-temperature-resistant and highly wear-resistant waterproof and breathable membrane. Background Art

[0002] In the manufacture of functional waterproof and breathable membranes, in order to balance the mechanical properties and functional characteristics of the material, a polymer casting solution is usually filled into a porous reinforced fiber skeleton, and then the polymer phase separation is caused by non-solvent-induced phase separation (NIPS) to form a waterproof and breathable membrane with a microporous structure. This method is known in the art as a wet film forming process.

[0003] The traditional wet-film process typically involves the following steps: uniformly filling the pores of a fiber reinforcement framework with a casting solution containing a polymer and a solvent, and then immersing the entire composite in a single coagulation bath containing a non-solvent. In the coagulation bath, the solvent in the casting solution rapidly diffuses into the non-solvent, causing the polymer's solubility to decrease rapidly and precipitate out of the solution, thereby forming a polymer matrix with a microporous structure within the pores of the reinforcement framework.

[0004] However, the interface between the polymer matrix and the reinforcing fiber skeleton ultimately formed by the high-performance waterproof and breathable membrane prepared by the existing technology mainly relies on weak physical entanglement and van der Waals forces for bonding, and lacks stable and strong covalent bonding. This physically weak interface causes the existing waterproof and breathable membrane to have major defects in high temperature resistance and wear resistance. Specifically, in subsequent processing that requires heat treatment (such as hot pressing of shoe materials) or when used in a high temperature environment, the polymer matrix and the reinforcing skeleton generate interfacial stress due to different thermal expansion coefficients. Since the interface strength of the physical bond is extremely low, it is impossible to effectively withstand and transmit this stress, resulting in micro-peeling and even macro-stratification at the interface, causing the waterproof and breathable membrane to lose its due structural integrity and functionality. In addition, the wear resistance of the material depends on the ability of all its components to synergistically resist external friction. In a waterproof and breathable membrane with a weak interface, when the surface is subjected to friction, the stress cannot be effectively transferred from the softer polymer matrix to the high-strength reinforcing fibers through a strong interface. This causes stress to concentrate on the surface of the substrate, causing it to wear out rapidly, and the reinforcing fibers are unable to play their due reinforcing and load-bearing roles due to failure to be effectively anchored, ultimately making the overall wear life of the waterproof and breathable membrane far lower than expected.

[0005] Therefore, how to improve the high temperature resistance and wear resistance of the functional waterproof and breathable membrane prepared by the wet film forming process is a key technical problem that needs to be solved urgently in this field. Summary of the Invention

[0006] The purpose of the present invention is to overcome the above-mentioned defects or problems existing in the background technology and provide a method for preparing a high-temperature resistant and highly wear-resistant waterproof and breathable membrane, which can improve the high-temperature resistance and wear resistance of the waterproof and breathable membrane prepared by the wet film forming process.

[0007] To achieve the above object, the present invention adopts the following technical solutions:

[0008] Technical Solution 1: A method for preparing a high-temperature resistant, highly wear-resistant waterproof and breathable membrane, which includes the following steps: Step 1: Filling a casting liquid containing a polyurethane resin and a solvent into the pores of a fiber skeleton having active groups on the surface to form a composite; Step 2: Immersing the composite in a first liquid environment composed of a mixture of ethanol and ethyl acetate to form a covalent bond interface between the fiber skeleton and the polyurethane resin; Step 3: Immersing the composite treated in Step 2 in a second liquid environment composed of a mixture of water and dimethylformamide to form a polyurethane matrix with a microporous structure in the pores of the skeleton.

[0009] Technical solution 2 based on technical solution 1: In the second liquid environment, the volume content of water is 65% to 75%.

[0010] Technical solution three based on technical solution one: Step two is carried out at a temperature of 20-40°C.

[0011] Technical solution 4 based on technical solution 1: Step 3 is carried out at a temperature of 5-10°C.

[0012] Technical solution five based on technical solution one: the fiber skeleton is a high-temperature resistant nanofiber skeleton, and its material is selected from polyimide, poly(p-phenylene benzobisoxazole) fiber, or polybenzimidazole.

[0013] Technical Solution 6 based on Technical Solution 1: The active group is an amino group or carboxyl group introduced on the surface of the polyimide or poly(p-phenylene benzobisoxazole) fiber through a surface modification process, or is a secondary amine group inherent in the polybenzimidazole material.

[0014] Technical solution seven based on technical solution one: the polyurethane resin is a bio-based polyurethane resin.

[0015] Technical solution eight based on technical solution one: the casting solution contains aluminum oxide particles and cellulose nanofibers.

[0016] Technical solution nine based on technical solution one: the filling in step one is cast into the fiber skeleton through a sizing curtain and uniform penetration is achieved through vacuum suction.

[0017] Technical solution 10 based on technical solution 1: After step 3, the method further includes a step of post-curing the formed waterproof and breathable membrane, and the post-curing treatment is selected from hot air drying, hot pressing or vacuum hot air drying.

[0018] From the above description of the present invention, it can be seen that compared with the prior art, the present invention has the following beneficial effects:

[0019] The preparation method of Technical Solution 1 fundamentally addresses the issues of insufficient high-temperature and wear resistance in existing wet-film processes due to weak interfacial bonding by precisely controlling the formation process of the waterproof and breathable membrane. This method first establishes the material basis for the interfacial chemical reaction in step 1: a fiber skeleton with surface reactive groups and a casting solution containing a polyurethane resin.

[0020] The core of this method lies in step two, immersing the composite in a first liquid environment formed by a mixture of ethanol and ethyl acetate. This liquid environment is a weak non-solvent system for the polyurethane resin, and its key role is that it can significantly slow down the rate of the physical process of macroscopic phase separation and precipitation of the polyurethane resin due to solvent exchange. This reduction in rate creates a necessary reaction window for interfacial chemical reactions, allowing the active groups on the surface of the fiber skeleton to have sufficient time to chemically react with the functional groups on the polyurethane resin molecular chain, thereby forming a stable and strong covalent bond interface between the two. This step changes the bonding properties of the interface, transforming the physically weak interface that is not heat-resistant and wear-resistant in the prior art into a chemically strong interface that can effectively withstand and transmit stress.

[0021] After establishing a strong chemical interface in step two, step three involves immersing the composite in a second liquid environment consisting of a mixture of water and dimethylformamide. This liquid environment is a strong non-solvent for the polyurethane resin, driving a vigorous and rapid phase separation of the polyurethane. Because the interface is pre-locked by covalent bonds and is not susceptible to disruption by violent physical processes, this step efficiently forms a through-hole microporous structure with specific functionality without compromising interfacial bonding strength.

[0022] Through the orderly implementation of the above three steps, the functional waterproof and breathable membrane prepared by this technical solution has a strong interface bonded by covalent bonds. This strong interface enables the waterproof and breathable membrane to effectively withstand and disperse the interfacial stress generated by different thermal expansion coefficients when subjected to heat treatment or high-temperature environments, thereby suppressing micro-peeling and macro-stratification at the interface and significantly improving the material's high-temperature resistance. At the same time, this strong interface also enables the waterproof and breathable membrane to effectively transfer stress from the relatively soft polyurethane matrix to the high-strength fiber skeleton when subjected to external friction, achieving coordinated load-bearing of the various components of the material, avoiding rapid wear caused by stress concentration on the matrix surface, and significantly improving the material's wear resistance.

[0023] Technical Solution 2, based on Technical Solution 1, further limits the volume content of water in the second liquid environment to 65% to 75%. This limitation is crucial to the overall performance of the final waterproof and breathable membrane. Precisely controlling the volume content of water within this range is key to achieving a rapid but controlled phase separation process, ensuring the stable formation of a uniform, finger-like microporous network that penetrates from the surface to the interior. This uniform, defect-free microporous network is not only the structural foundation for the waterproof and breathable membrane to achieve high moisture permeability and excellent waterproof performance, but its complete structural morphology also avoids stress concentration points caused by internal defects, thereby enhancing the structural stability of the waterproof and breathable membrane when subjected to thermal cycling or mechanical friction, providing structural support for the material's high temperature resistance and wear resistance.

[0024] Based on Technical Solution 1, Technical Solution 3 further limits the temperature of Step 2 to 20-40°C. This temperature range is a precise control of the kinetics of interfacial chemical reactions, which is directly related to the quality and integrity of the covalent bond interface. Within this limited temperature range, the optimal activation energy can be provided for the reaction between the active groups on the surface of the fiber skeleton and the polyurethane functional groups. The optimal reaction temperature range of 20-40°C is a key process condition to ensure that interfacial covalent bonds can be formed efficiently, fully and specifically. A more complete and stronger covalent bond interface means stronger interfacial bonding strength, which provides the most solid guarantee for the waterproof and breathable membrane to ultimately obtain excellent high temperature resistance and wear resistance.

[0025] Based on Technical Solution 1, Technical Solution 4 further limits the temperature of step 3 to 5-10°C. This limitation is a further optimization of the nucleation and growth dynamics during the rapid phase separation process. In a strong non-solvent system, a lower temperature can significantly increase the supersaturation of the polymer solution, thereby greatly increasing the nucleation rate, which is conducive to the formation of a microporous structure with smaller size and more uniform distribution. This highly uniform microstructure improves the consistency of the macroscopic performance of the final product and reduces the weak points inside the material. This structural uniformity is crucial to improving the durability of the material because it enhances the material's ability to resist local stress concentration, thereby helping to improve the structural stability of the waterproof and breathable membrane in high temperature environments and its wear resistance under long-term friction.

[0026] Technical Solution 5, based on Technical Solution 1, further limits the material of the fiber skeleton to polyimide, poly(p-phenylene benzobisoxazole) fiber, or polybenzimidazole. These selected materials are all high-performance specialty polymer fibers, which are the cornerstones for the entire waterproof and breathable membrane to achieve high temperature resistance and high wear resistance. The glass transition temperature and thermal decomposition temperature of these fiber materials themselves are much higher than those of conventional polymers, ensuring that the skeleton itself will not soften or degrade in high temperature environments, providing stable structural support for the waterproof and breathable membrane. In addition, these materials also have extremely high tensile modulus and strength. Under the strong interface effect of the present invention, they can serve as the main load-bearing unit, thereby giving the final product excellent overall mechanical properties and forming the basis for achieving high wear resistance.

[0027] Technical Solution 6, building on Technical Solution 5, further clarifies the source of the active groups. This definition is the technical prerequisite for achieving the interfacial chemical bonding described in Technical Solution 1, and it clearly illustrates the specific chemical pathway for forming the covalent bond interface. By specifying the specific chemical mechanism for covalent bond formation, this not only greatly enhances the logical rigor and technical reliability of the technical solution, but also ensures that the resulting interfacial covalent bonds have a higher density and stronger binding force. A strong interface with a clear and reliable chemical mechanism is the direct guarantee for the waterproof and breathable membrane to achieve excellent high-temperature resistance and wear resistance.

[0028] Technical Solution 7, building on Technical Solution 1, further limits the polyurethane resin to bio-based polyurethane resins. The core value of this limitation lies in ensuring all the high-performance attributes of the waterproof and breathable membrane while also ensuring the product's environmental friendliness and sustainable development. This invention demonstrates that its core gradient coagulation bath process is also applicable to bio-based polymer systems. This results in a high-temperature, wear-resistant waterproof and breathable membrane that not only meets stringent functional requirements but also aligns with the inevitable global manufacturing transition toward green and low-carbon development, enhancing the product's market competitiveness and social value.

[0029] Technical Solution 8 is based on Technical Solution 1, and further adds aluminum oxide particles and cellulose nanofibers to the casting liquid. This limitation constructs a more complex composite reinforcement system by introducing a multi-scale reinforcement phase, thereby improving the wear resistance and high temperature resistance of the material in multiple dimensions. As an inorganic ceramic particle with high hardness and high thermal stability, aluminum oxide can be directly used as a wear-resistant hard point when dispersed in the polyurethane matrix. When the surface of the material is rubbed, it preferentially bears and resists external wear, significantly improving the scratch resistance and wear life of the waterproof and breathable membrane. At the same time, cellulose nanofibers, as a nano-scale reinforcement, can form a fine reinforcement network inside the polyurethane matrix, improving the cohesive strength and toughness of the matrix itself, thereby forming a multi-scale synergistic reinforcement effect with the fiber skeleton, further improving the overall mechanical strength and fatigue resistance of the waterproof and breathable membrane.

[0030] Based on Technical Solution 1, Technical Solution 9 further limits the specific filling method in Step 1, namely casting through a sizing curtain combined with vacuum suction. This limitation optimizes and guarantees the process and is an important prerequisite for obtaining high-quality products. This combination effectively solves common process defects such as uneven filling and residual bubbles. A defect-free and uniform composite is the basis for the success of all subsequent steps. It ensures that the formed covalent bond interface is continuous and complete, and the formed microporous structure is uniform. This structural integrity avoids stress concentration caused by defects, which is crucial to ensuring the performance reliability of the final product under high temperature and wear conditions, and is the process guarantee for achieving its excellent high temperature resistance and wear resistance.

[0031] Technical Solution 10 adds a post-curing step to Technical Solution 1. This step is the final and indispensable step in the transition of a waterproof and breathable membrane from laboratory preparation to an industrialized finished product, and is crucial for ensuring the stability and durability of product performance. Post-curing effectively removes residual solvent from the waterproof and breathable membrane, releases the internal stress generated during the film-forming process, and locks in the microporous structure. A waterproof and breathable membrane with no residual solvent, no internal stress, and a stable structure can maintain its dimensional stability and mechanical properties in high-temperature environments and exhibit consistent wear-resistant behavior under long-term friction. Therefore, post-curing is a necessary step to ensure the stable and lasting high-temperature and wear-resistant properties of the waterproof and breathable membrane. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0033] Figure 1 This is a scanning electron microscope image 1 of the waterproof and moisture-permeable membrane prepared in Example 1 of the present invention;

[0034] Figure 2 Scanning electron microscope image 2 of the waterproof and moisture-permeable membrane prepared in Example 1 of the present invention;

[0035] Figure 3 This is a scanning electron microscope image 3 of the waterproof and moisture-permeable membrane prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0036] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are preferred embodiments of the present invention and should not be regarded as excluding other embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts shall fall within the scope of protection of the present invention.

[0037] In the claims, description and drawings of the present invention, unless otherwise clearly defined, the use of terms such as "first", "second" or "third" is for the purpose of distinguishing different objects rather than for describing a specific order.

[0038] In the claims, specification and the above-mentioned drawings of the present invention, unless otherwise expressly defined, directional words such as the terms "center", "transverse", "longitudinal", "horizontal", "vertical", "top", "bottom", "inside", "outside", "up", "down", "front", "back", "left", "right", "clockwise", "counterclockwise" and the like indicating directions or positional relationships are based on the directions and positional relationships shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific direction or be constructed and operated in a specific direction, and therefore cannot be understood as limiting the specific scope of protection of the present invention.

[0039] In the claims, description and above-mentioned drawings of the present invention, unless otherwise expressly defined, the terms "fixed connection" or "fixed connection" should be understood in a broad sense, that is, any connection method without displacement relationship and relative rotation relationship between the two parties, that is, including non-detachable fixed connection, detachable fixed connection, integral connection and fixed connection through other devices or elements.

[0040] In the claims, description and drawings of the present invention, if the terms "include", "have" and their variations are used, they are intended to mean "including but not limited to".

[0041] The present invention relates to a method for preparing a high-temperature resistant and highly wear-resistant waterproof and breathable membrane, which comprises the following steps: step 1: filling a casting liquid containing a polyurethane resin and a solvent into the pores of a fiber skeleton having active groups on the surface to form a composite; step 2: immersing the composite in a first liquid environment formed by a mixture of ethanol and ethyl acetate to form a covalent bond interface between the fiber skeleton and the polyurethane resin; and step 3: immersing the composite treated in step 2 in a second liquid environment formed by a mixture of water and dimethylformamide to form a polyurethane matrix with a microporous structure in the pores of the skeleton.

[0042] The volume content of water in the second liquid environment is 65% to 75%. Step 2 is performed at a temperature of 20-40°C. Step 3 is performed at a temperature of 5-10°C. Specifically, in a preferred embodiment, the temperature of the first liquid environment is 25°C, the temperature of the second liquid environment is 5°C, and the volume content of water in the second liquid environment is 70%.

[0043] Furthermore, the fiber skeleton is a high-temperature-resistant nanofiber skeleton, whose material is selected from polyimide, poly(p-phenylene benzobisoxazole) fiber, or polybenzimidazole. Specifically, the high-temperature-resistant nanofiber skeleton has a porosity of 70-95% and an average pore size of 10-500 nm, ensuring sufficient penetration of the casting solution and providing sufficient space for the final microporous structure.

[0044] The active groups are amino or carboxyl groups introduced on the surface of the polyimide or poly(p-phenylene benzobisoxazole) fiber through a surface modification process, or are secondary amine groups inherent in the polybenzimidazole material. Specifically,

[0045] The polyurethane resin is a bio-based polyurethane resin. Specifically, to introduce amino groups, the polyimide nanofiber membrane can be immersed in a 5% by mass 3-aminopropyltriethoxysilane (APTES) ethanol solution and treated at 60°C for 30 minutes. To introduce carboxyl groups, the poly(p-phenylene benzobisoxazole) fiber can be immersed in a 65% by mass concentrated nitric acid and oxidized at 80°C for 1 hour. The bio-based polyurethane resin has a bio-based content of not less than 60% as determined by ASTM D6866. The resin is prepared by reacting a bio-based polyester polyol (e.g., formed by the polycondensation of bio-based succinic acid and bio-based 1,4-butanediol) with diphenylmethane diisocyanate (MDI).

[0046] The casting solution contains aluminum oxide particles and cellulose nanofibers. Specifically, the casting solution is prepared by uniformly mixing a bio-based polyurethane resin, 1.0% to 3.0% aluminum oxide particles (average particle size 50-100 nm) representing the total dry weight of the resin, 0.5% to 2.0% cellulose nanofibers representing the total dry weight of the resin, and 0.1% to 0.5% penetrant OT-50 (sodium dioctyl sulfosuccinate) representing the total dry weight of the resin, in dimethylformamide (DMF) as the main solvent.

[0047] The filling process in step 1 is performed by casting the casting solution onto the fiber skeleton using a sizing curtain and achieving uniform penetration through vacuum suction. Specifically, the filling process uses a sizing curtain with a slit width of 0.5 mm to evenly coat the surface of the fiber skeleton with the casting solution. Simultaneously, vacuum assistance is applied on the other side of the skeleton, and the absolute pressure of the system is controlled within the range of 20 kPa to 50 kPa to ensure that the casting solution quickly and bubble-free penetrates the internal pores of the skeleton.

[0048] Furthermore, after step 3, the method further includes a step of post-curing the formed waterproof and breathable membrane. The post-curing treatment is selected from hot air drying, hot pressing, or vacuum hot air drying. Specifically, hot air drying can be performed at 80°C for 2 minutes; hot pressing can be performed at 90°C and a pressure of 0.5 MPa for 3 minutes; and vacuum hot air drying can be performed at 70°C for 5 minutes.

[0049] The present invention relates to a method for preparing a high-temperature-resistant, highly wear-resistant waterproof and breathable membrane. By precisely controlling the membrane's formation process, the method fundamentally addresses the problem of insufficient high-temperature and wear resistance in existing wet-process membrane formation processes due to weak interfacial bonding. The method first establishes the material basis for interfacial chemical reactions in step 1: a fiber skeleton with surface reactive groups and a casting solution containing a polyurethane resin. The core of the method lies in step 2: immersing the composite in a first liquid environment composed of a mixture of ethanol and ethyl acetate. This liquid environment, a weak non-solvent for the polyurethane resin, significantly slows the rate of macroscopic phase separation and precipitation of the polyurethane resin due to solvent exchange. This reduced rate creates a necessary reaction window for the interfacial chemical reaction, allowing the reactive groups on the fiber skeleton surface ample time to react with the functional groups on the polyurethane resin molecular chains, thereby forming a stable and strong covalent bond interface between the two. This step alters the interfacial bonding properties, transforming the physically weak interface, which is not heat-resistant and wear-resistant in the prior art, into a chemically strong interface capable of effectively withstanding and transmitting stress. After a strong chemical interface is constructed in step two, step three is to immerse the complex in a second liquid environment formed by a mixture of water and dimethylformamide. The liquid environment is a strong non-solvent system for polyurethane resin, which can drive the polyurethane to undergo violent and rapid phase separation. Since the interface has been pre-locked by covalent bonds and is not afraid of being destroyed by violent physical processes, this step can efficiently form a through-microporous structure with specific functionality without compromising the interfacial bonding strength. Through the orderly implementation of the above three steps, the functional waterproof and breathable membrane prepared by this technical solution has an interface that is a strong interface bonded by covalent bonds. This strong interface enables the waterproof and breathable membrane to effectively withstand and disperse the interfacial stress generated by different thermal expansion coefficients when subjected to heat treatment or high-temperature environment, thereby suppressing the micro-peeling and macro-stratification of the interface and significantly improving the high-temperature resistance of the material. At the same time, this strong interface also enables the waterproof and breathable membrane to effectively transfer stress from the softer polyurethane matrix to the high-strength fiber skeleton when subjected to external friction, achieving coordinated load-bearing of the various components of the material, avoiding rapid wear caused by stress concentration on the matrix surface, and thus significantly improving the wear resistance of the material.

[0050] In order to further illustrate the advantages of the technical solutions of the present invention, the following examples and comparative examples are provided.

[0051] Raw materials used in the examples

[0052] Polyimide (PI) nanofiber skeleton: purchased from Jiangsu Shunyi Composite Materials Co., Ltd., China, with the brand name SY-PI-NFM-20, porosity of 85%, and average pore size of 200 nm.

[0053] Poly(p-phenylene benzobisoxazole) fiber (PBO) nanofiber skeleton: purchased from Toyobo Co., Ltd., Japan, brand: AS, a skeleton with a porosity of 80% and an average pore size of 300 nm, was produced by laboratory electrospinning process.

[0054] Polybenzimidazole (PBI) nanofiber skeleton: purchased from PBI Performance Products, Inc., USA, brand PBI was made into a skeleton with a porosity of 90% and an average pore size of 400 nm by laboratory electrospinning process.

[0055] Bio-based polyurethane (BPU) resin: purchased from China Wanhua Chemical Group Co., Ltd., brand WHT-B85A, 62% biobased content, 30% solids solution in DMF.

[0056] 3-Aminopropyltriethoxysilane (APTES): purchased from Dow Chemical Company (Dow), brand DOWSIL TM Z-6011Silane.

[0057] Alumina (Al2O3) particles: purchased from China Aladdin Biochemical Technology Co., Ltd., brand A108848, spherical, with an average particle size of 80 nm.

[0058] Cellulose nanofiber (CNC): purchased from China Zhongke Xianxing (Suzhou) Nanotechnology Co., Ltd., brand XFN-CNC-01, 5% aqueous dispersion.

[0059] Penetrant OT-50: purchased from BASF, Germany, brand A-BO.

[0060] Other reagents: ethanol, ethyl acetate, dimethylformamide (DMF), and concentrated nitric acid were all analytical grade and purchased from China National Pharmaceutical Group Chemical Reagent Co., Ltd.

[0061] Example 1

[0062] This embodiment relates to a method for preparing a high-temperature resistant and highly wear-resistant waterproof and breathable membrane, and the specific steps are as follows:

[0063] Step 1: Filling a casting solution containing a polyurethane resin and a solvent into the pores of a fiber skeleton having active groups on the surface to form a composite.

[0064] First, the PI nanofiber skeleton was surface-modified by immersing it in a 5% (by weight) APTES ethanol solution and stirring it at 60°C for 30 minutes to graft amino-active groups onto the fiber surface. The fiber was then washed three times with anhydrous ethanol and dried in a vacuum oven at 60°C for 2 hours.

[0065] Then, a casting solution was prepared: 1.5 parts of Al2O3 particles, 1 part of water-dispersed CNC (converted to dry weight), and 0.2 parts of penetrant OT-50 were added to 100 parts of BPU resin solution, and the mixture was mixed evenly under high-speed stirring to obtain a casting solution.

[0066] Finally, filling is carried out: a sizing curtain with a slit width of 0.5 mm is used to evenly coat the casting liquid on the surface of the modified PI fiber skeleton. At the same time, vacuum assistance is applied on the other side of the skeleton, and the absolute pressure of the system is controlled at 30 kPa to achieve uniform penetration.

[0067] Step 2: Immersing the composite into a first liquid environment formed by mixing ethanol and ethyl acetate to form a covalent bond interface between the fiber skeleton and the polyurethane resin.

[0068] The complex obtained in step 1 was immersed in a first liquid environment prepared by mixing ethanol and ethyl acetate in a volume ratio of 3:1, and treated in the liquid environment at a temperature of 25° C. for 2 minutes.

[0069] Step 3: Immersing the composite body treated in step 2 into a second liquid environment consisting of a mixture of water and dimethylformamide to form a polyurethane matrix with a microporous structure in the pores of the skeleton.

[0070] The composite treated in step 2 was immediately immersed in a second liquid environment prepared by mixing water and DMF at a volume ratio of 7:3, and treated in the liquid environment at a temperature of 5° C. for 3 minutes.

[0071] Step 4: Post-curing the formed waterproof and breathable membrane.

[0072] The wet film obtained in step 3 was dried in a hot air circulation oven at 80° C. for 2 minutes to obtain the final high temperature resistant, highly wear-resistant, waterproof and breathable film.

[0073] Example 2

[0074] This embodiment is basically the same as the first embodiment, except that:

[0075] In step 1, a PBO nanofiber skeleton was used. Its surface modification process involved immersing the PBO nanofiber skeleton in 65% concentrated nitric acid and oxidizing it at 80°C for one hour to introduce reactive carboxyl groups onto the fiber surface. After removal, the skeleton was repeatedly rinsed with copious amounts of deionized water until the rinse water was neutral, and then dried in a vacuum oven at 80°C.

[0076] The post-curing treatment in step 4 is: hot pressing at 90° C. and a pressure of 0.5 MPa for 3 minutes.

[0077] Example 3

[0078] This embodiment is basically the same as the first embodiment, except that:

[0079] In step 1, a PBI nanofiber skeleton is used. Since its molecular structure contains secondary amine active groups, no additional surface modification treatment is required.

[0080] The first liquid environment in step 2 is a mixture of ethanol and ethyl acetate in a volume ratio of 4:1, and the processing temperature is 20°C.

[0081] The second liquid environment in step 3 is a mixture of water and DMF in a volume ratio of 6.5:3.5, and the treatment temperature is 10°C.

[0082] Comparative Example 1

[0083] This comparative example is used to illustrate the necessity of the gradient coagulation bath process of the present invention.

[0084] The preparation method was essentially the same as that of Example 1, except that step 2 was skipped. Specifically, after step 1, the composite was directly immersed in a second liquid environment consisting of a mixture of water and DMF at a volume ratio of 7:3, treated in this liquid environment at 5°C for 3 minutes, and then subjected to the same post-curing treatment.

[0085] Comparative Example 2

[0086] This comparative example is used to illustrate the necessity of the surface active groups of the fiber skeleton.

[0087] The preparation method is basically the same as that of Example 1, except that the PI nanofiber skeleton used in step 1 has not undergone any surface modification treatment, that is, its surface does not have grafted amino active groups. All other steps are exactly the same as those of Example 1.

[0088] Performance testing and results

[0089] The performance of the waterproof and moisture-permeable membranes prepared in Examples 1-3 and Comparative Examples 1-2 was tested. The test methods and results are shown in the following table.

[0090] Test standard:

[0091] 1. Interface bonding strength: Refer to GB / T 2790-1995 (Adhesive 180° peel strength test method - Flexible material to rigid material) and perform a peel test on the PU matrix and fiber skeleton.

[0092] 2. High temperature resistance (appearance after heat treatment at 180°C): Place the sample in an oven at 180°C for 30 minutes, take it out and cool it down, and observe its appearance changes to evaluate whether there is delamination, blistering, shrinkage, etc.

[0093] 3. Wear resistance (mass loss): Referring to GB / T 10408-2000 (Plastics Abrasion Test - Taber Method), use a CS-10 grinding wheel, apply a 1000g load, and test the mass loss after 1000 cycles.

[0094] 4. Water vapor transmission rate: refer to GB / T 12704.2-2009 (Test method for water vapor permeability of textile fabrics Part 2:

[0095] Evaporation method), tested at 38°C and 90% RH.

[0096] 5. Hydrostatic pressure: Refer to GB / T 4744-2013 (Testing and evaluation of waterproof performance of textiles - Hydrostatic pressure method).

[0097] Performance test results table:

[0098]

[0099] The data in the table above demonstrate that the interfacial bonding strength of the waterproof and breathable membranes prepared in Examples 1-3 is significantly greater than that of Comparative Examples 1 and 2, demonstrating that the gradient coagulation bath process and the provision of surfactant groups in the present invention significantly enhance interfacial bonding. Consequently, the samples of Examples 1-3 maintain intact structure, excellent wear resistance, and minimal mass loss after high-temperature treatment at 180°C, fully demonstrating that the present invention effectively addresses the issues of insufficient high-temperature and wear resistance noted in the prior art.

[0100] Comparative Example 1 lacks the crucial step of forming a covalent bond interface, resulting in extremely weak interfacial bonding, leading to severe delamination at high temperatures and the worst wear resistance. Although Comparative Example 2 employed a gradient coagulation bath, the absence of active groups on the skeleton surface prevented effective chemical bonding. While its performance was superior to that of Comparative Example 1, it was still significantly inferior to the examples of the present invention.

[0101] In addition, all samples maintained excellent waterproof and moisture permeability, indicating that the present invention significantly improved the high temperature resistance and wear resistance without sacrificing the original core functions of the material.

[0102] In addition, Figure 1 、 2 3 are scanning electron microscope (SEM) images of the waterproof and breathable membrane prepared by Example 1 of the present invention, which intuitively confirm from the microstructure that the present invention can achieve the above-mentioned excellent technical effects.

[0103] Attachment Figure 2 and attached Figure 3 It is a cross-sectional view of a waterproof and breathable membrane. It can be clearly seen from the figure that the polyurethane matrix has completely and evenly penetrated and filled into the pores of the fiber skeleton. The most critical thing is that between the polyurethane matrix and each independent nanofiber, the two are tightly fitted to form a seamless, gapless interface. This microstructure is a direct reflection of the present invention's preferential formation of a covalent bond interface through step 2. It is precisely because of the presence of this strong chemical interface that when the material is subjected to a peel test, the destructive force is difficult to easily expand along the interface, thereby showing an extremely high interfacial bonding strength (such as 25.8N / 25mm in Example 1). Similarly, when subjected to a high temperature treatment of 180°C, this defect-free strong interface can effectively withstand and transmit the interfacial stress generated by the different thermal expansion coefficients, avoiding the generation and expansion of micro cracks, making it appear "intact and unchanged" on a macro scale. In contrast, Comparative Examples 1 and 2 lack this strong interface, and there are a large number of micro defects at their interfaces, which can easily expand into macroscopic delamination and peeling under the action of thermal stress.

[0104] Attachment Figure 2 and attached Figure 3 The complete and dense composite structure shown also explains the excellent wear resistance of the material. Under the action of friction, external stress can be effectively transferred from the softer polyurethane matrix to the high-strength and high-hardness PI fiber skeleton through this seamless strong interface. As the main load-bearing phase, the fiber skeleton works synergistically with the matrix to resist external wear. In the comparative example, due to the weak interface bonding, the stress cannot be effectively transmitted, resulting in the friction force concentrated on the softer matrix surface, causing it to be rapidly worn, resulting in huge quality losses.

[0105] Attachment Figure 1 This is a surface diagram of the waterproof and breathable membrane. As can be seen from the figure, although the polyurethane matrix has been filled with a fiber network, the surface of the entire membrane still maintains an open porous structure, which provides an effective diffusion channel for water vapor molecules and enables the material to have a high water vapor permeability (such as 8550g / m 2 At the same time, the polyurethane matrix formed in step 3 itself has a microporous structure. The pore size of these pores is much smaller than that of liquid water droplets, thus effectively preventing the penetration of liquid water, thereby ensuring the high hydrostatic pressure performance of the material.

[0106] The above description and embodiments are intended to explain the scope of protection of the present invention, but do not constitute a limitation thereto. Modifications, equivalent substitutions, or other improvements to the embodiments of the present invention or portions thereof that can be obtained by a person of ordinary skill in the art through logical analysis, reasoning, or limited experimentation based on the teachings of the present invention or the above embodiments, combined with common knowledge, ordinary technical knowledge in the field, and / or prior art, should all be included within the scope of protection of the present invention.

Claims

1. A method for preparing a high-temperature resistant and highly wear-resistant waterproof and breathable membrane, characterized in that: The following steps are involved: Step 1: Filling a casting solution containing a polyurethane resin and a solvent into the pores of a fiber skeleton having active groups on its surface to form a composite; Step 2: immersing the composite in a first liquid environment of a mixture of ethanol and ethyl acetate to form a covalent bond interface between the fiber skeleton and the polyurethane resin; Step 3: Immersing the composite body treated in step 2 into a second liquid environment consisting of a mixture of water and dimethylformamide to form a polyurethane matrix with a microporous structure in the pores of the skeleton.

2. The method for preparing a high-temperature resistant and highly wear-resistant waterproof and breathable membrane according to claim 1, characterized in that: The volume content of water in the second liquid environment is 65% to 75%.

3. The method for preparing a high-temperature resistant and highly wear-resistant waterproof and breathable membrane according to claim 1, characterized in that: The step 2 is carried out at a temperature of 20-40°C.

4. The method for preparing a high-temperature resistant and highly wear-resistant waterproof and breathable membrane according to claim 1, characterized in that: The step 3 is carried out at a temperature of 5-10°C.

5. The method for preparing a high-temperature resistant and highly wear-resistant waterproof and breathable membrane according to claim 1, characterized in that: The fiber skeleton is a high-temperature resistant nanofiber skeleton, and its material is selected from polyimide, poly(p-phenylene benzobisoxazole) fiber, or polybenzimidazole.

6. The method for preparing a high-temperature resistant and highly wear-resistant waterproof and breathable membrane according to claim 5, characterized in that: The active groups are amino groups or carboxyl groups introduced onto the surface of the polyimide or poly(p-phenylene benzobisoxazole) fiber through a surface modification process, or are secondary amine groups inherent in the polybenzimidazole material.

7. The method for preparing a high-temperature resistant and highly wear-resistant waterproof and breathable membrane according to claim 1, characterized in that: The polyurethane resin is a bio-based polyurethane resin.

8. The method for preparing a high-temperature resistant and highly wear-resistant waterproof and breathable membrane according to claim 1, characterized in that: The casting solution contains aluminum oxide particles and cellulose nanofibers.

9. The method for preparing a high-temperature resistant and highly wear-resistant waterproof and breathable membrane according to claim 1, characterized in that: The filling in step 1 is cast into the fiber skeleton through a sizing curtain and uniformly penetrated by vacuum suction.

10. The method for preparing a high-temperature resistant and highly wear-resistant waterproof and breathable membrane according to claim 1, characterized in that: After step three, the method further comprises a step of post-curing the formed waterproof and breathable membrane, wherein the post-curing treatment is selected from hot air drying, hot pressing or vacuum hot air drying.

Citation Information

Patent Citations

  • High-strength polyurethane waterproof and moisture-permeable film and preparation method thereof

    CN111705430A

  • Bio-based polyurethane waterproof moisture-permeable film and preparation method thereof

    CN119083195A

  • Polymer or polymer composite membrane having through-thickness micropores, and method for preparing same

    US20120325737A1